The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7771/2159-6670.1150
|View full text |Cite
|
Sign up to set email alerts
|

VFR-into-IMC: An Analysis of Two Training Protocols on Weather-Related Posttest Scores

Abstract: According to the Aircraft Owners and Pilots Association Air Safety Institute, 264 accidents were identified as continued visual flight rules (VFR) into instrument meteorological conditions (IMC), during the past ten years. Approximately 89% of those VFR-into-IMC accidents were fatal, causing hundreds of deaths. VFR-into-IMC has been a major concern for the general aviation community, prompting focused efforts. Research, data analyses, outreach, training, and education are recommended practices to address risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Effective ADM is a vital aspect of risk management in aviation, without which superior results cannot be achieved. A large amount of research has indicated that ADM is trainable (Buch, 1984;Jensen, 1987;Keller, 2015;Li & Harris, 2001;O'Hare et al, 2009). Pilots frequently make critical decisions to mitigate the inherent risks affecting aviation safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective ADM is a vital aspect of risk management in aviation, without which superior results cannot be achieved. A large amount of research has indicated that ADM is trainable (Buch, 1984;Jensen, 1987;Keller, 2015;Li & Harris, 2001;O'Hare et al, 2009). Pilots frequently make critical decisions to mitigate the inherent risks affecting aviation safety.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that ADM training can improve pilots' risk management knowledge and skills. Keller et al (2017) Findings showed that the participants who reflected on a set of cases involving pilots flying into adverse weather conditions and ADM concepts made safer and more timely decisions than other participants who only recalled the material. The authors concluded that case reflection during pilots' ADM training could improve aviation safety.…”
Section: Aeronautical Decision Makingmentioning
confidence: 93%
See 1 more Smart Citation
“…Knecht, Ball, and Lenz (2010) determined that video instruction with pilots was not effective, possibily because of the complexity of the material and lack of interaction with the video. Keller, Carney, Xie, Major, and Price (2017) determined that interactive training modules did not significantly increase post-test weather knowledge scores; however, no investigation was done on whether or not the modules improved pilot's situation awareness or decision making. This research will investigate the effect of an ExpEd module (estimating visibility) on the situation awareness and decision-making of general aviation pilots.…”
Section: Experiential Educationmentioning
confidence: 99%
“…Taxonomy V1.0 can be used to develop traceable pilot education and training protocols for particularly challenging aviation weather problems, such as VFR into IMC. This problem has received a great deal of attention from a number of several researchers (for example, see the literature review in Keller, Carney, Xie, Major, & Price, 2017). There has also been interest in testing different types of simulation tools for determining their efficacy in helping pilots detect the danger and react to it faster (e.g., Whitehurst, Brown, Rantz, Nicolai, & Bradley, 2019).…”
Section: A Weather Taxonomy For Use In Ga Pilot Education and Trainingmentioning
confidence: 99%